Do Female Songbirds Avoid a Mammalian Nest Predator When Selecting Their Nest Site? - Vernouillet, Alizée; Fortin, Marie-Josée; Fiola, Marie-Line; Villard, Marc-André (Frontiers in Ecology and Evolution, 2020)
Perceived predation risk can elicit strong behavioral responses in potential prey. During nest building, songbirds exhibit anti-predator behaviors under experimental conditions. Here, we hypothesized that females of two ground-nesting songbird species, the Ovenbird (Seiurus aurocapilla) and the Hermit Thrush (Catharus guttatus), would use naturally-available cues of predation risk when selecting their nest site, thereby avoiding activity hotspots of Eastern Chipmunks (Tamias striatus), a predator on songbird nests and fledglings. Chipmunks are highly vocal, thus providing cues of their presence. We mapped chipmunk detections and songbird nests over four successive years in study plots located in mature deciduous forest of New Brunswick, Canada. Chipmunk activity varied by an order of magnitude among study plots and years. Nests were built further away from chipmunk detections than expected by chance in some, but not all, plot-year combinations. When comparing study plots, the proportion of nests built within hotspots of chipmunk activity was four times lower in the two plots where chipmunk activity was highest. Yet, we did not find clear evidence that chipmunk avoidance provided fitness benefits, possibly because this behavior procured little protection at high chipmunk densities. The persistence of this avoidance behavior in our focal species of ground-nesting songbirds might be linked to the benefits it procures at intermediate chipmunk densities.